2022
DOI: 10.1088/1361-6498/ac34a1
|View full text |Cite
|
Sign up to set email alerts
|

Current status of eye-lens dosimetry in Canada

Abstract: For occupational exposures in planned exposure situations International Commission on Radiological Protection (ICRP) publication 118 recommends an equivalent dose limit for the lens of the eye of 20 mSv yr−1 averaged over five years with no single year exceeding 50 mSv. This constitutes a reduction from the previous limit of 150 mSv yr−1. The Canadian nuclear regulator, the Canadian Nuclear Safety Commission, responded to the ICRP recommendation by initiating amendments to the Radiation Protection Regulations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…For whole-body exposures in occupational settings, thermoluminescent and optically stimulated luminescence technologies are typically used to measure dose from X ray, gamma ray, and beta exposures and CR-39 nuclear track detectors are used to measure dose from neutron exposures ( 57 ). With respect to the eye lens dosimetry measurements, Dubeau et al ( 58 ) provides a detailed description of available eye lens dosimeters that seek to measure H p (3), personal dose equivalent delivered to a 3 mm depth in an ICRU cylindrical or slab phantom. H p (3) is an operational quantity that seeks to closely approximate the dose equivalent delivered to the eye lens ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For whole-body exposures in occupational settings, thermoluminescent and optically stimulated luminescence technologies are typically used to measure dose from X ray, gamma ray, and beta exposures and CR-39 nuclear track detectors are used to measure dose from neutron exposures ( 57 ). With respect to the eye lens dosimetry measurements, Dubeau et al ( 58 ) provides a detailed description of available eye lens dosimeters that seek to measure H p (3), personal dose equivalent delivered to a 3 mm depth in an ICRU cylindrical or slab phantom. H p (3) is an operational quantity that seeks to closely approximate the dose equivalent delivered to the eye lens ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Commercially available eye lens dosimeters were deemed to provide a satisfactory response to photon radiation, while the response to beta radiation requires improvement ( 60 ). In addition, Dubeau et al ( 58 ) found for neutron eye lens dosimetry, that a selection of commercially available passive neutron dosimeters exists, however their ability to accurately measure neutron eye lens dose has yet to be evaluated. Another study by Dubeau et al ( 61 ) tested the response of five commercially available skin dosimeters each covered by a 300 mg cm –2 thick layer of polycarbonate.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated in a recent paper [35], direct monitoring using a dedicated proven H p (3) dosimeter is the preferred method for assessing and ascertaining dose to the lens of the eye. However, in case of unavailability of such a dosimeter, alternative methods may be used when applicable (e.g.…”
Section: Determination Of H P (3) Using Alternate Methods (Eg Use Of ...mentioning
confidence: 99%